BOOK REVIEW “LIFE OF PI” BY YANN MARTEL - Tampubolon, Bernand Mardianus (LANTERN (Journal on English Language, Culture and Literature), 2016)
This book review is written to find the strength and the weakness in Life of Piwhich is written by Yann Martel. “The Book Review of Life of Pi” is focusing on the content of the novel finding the strength and the weakness.  The strengths are the plot and the main character named Pi, the weakness is the end of the novel. The plot conveys how the author describes all situations in this novel clearly and the main character shares readers about how to face the world and Pi shares lots of values in his life as a tough boy. The weakness is the end of the novel, Martel does not give an explanation about why Richard dumps Pi without saying goodbye at all. This novel conveys about anything that people think. A novel does not deliver any knowledge of life, but in this novel I read many valuable words.